(untitled) (Journal of the College of Education for Women, 2019)
This investigation was carried out to examin the effect of addition of dried bread (db) in different percentages on the sensory and microbial properties of the Chickpeas with Tehena (C T) . The results revealed that adding 0% (than db in the CT) ( treatment A ) control gained high significan different than that of other adding percentages in texture and appearance . And showed that of adding 5% (than db in the CT) (treatment B ) gained high significan different than that of other adding percentages in flavor , colour and overall acceptance. The adding 15% (than db in the CT) ( treatment C) showed that gained high significan different than adding 25 and 35 % (than db in the CT) (treatments D and E ) than all sensory properties . And adding D gained high significan different than that of adding E in appearance . And did not show significant differences between adding A and B than all sensory properties and between adding D and E in texture , flavor , colour and overall acceptance and between adding A and C in flavor . In regards with microbial tests it was , found that of bacteria Baicllus appeared in low numbers, which amount to 4 the unit cell bacterial cfu / ml in the E after freezing for 1.5 day at -18 Cº and dissolution for 1 o’clock at 25 Cº . Did not show bacteria , molds and yeasts in other adding percentages . And show bacteria E.coli appeared in the A and B , which amount to 75 and 6 cfu / ml . and did not show in other adding percentages . The also showed bacteria Baicllus appeared in the B , C and D , which amount to 200 , 140 and 13 cfu / ml . And did not show in the A and E after stored for 4 days at 4 Cº and to leave for 2 o, clock at 30 Cº . It can be concluded that the best adding from the overall acceptance 5% (than db in the CT) . And the best adding from the stored for 4 days at 4 Cº and to leave for 2 o’clock 35% (than db in the CT) . Therefore , the dried bread are considered sensory accepted materials as well as inhibitors of bacteria and molds in the Chickpeas with Tehena stored at 4Cº for 4 days , representation materials connection of free water was found in the Chickpeas with Tehena .